A novel homozygous CYP17A1 mutation causes partial 17 α-hydroxylase/17, 20-lyase deficiency in 46, XX: a case report and literature review. (31st December 2023) - Chen, Heye; Chen, Yingting; Mao, Hongxian; Huang, Huaying; Lou, Xueyong
Abstract: Aim: 17 α-hydroxylase/17, 20-lyase deficiency (17-OHD) is an extremely rare autosomal recessive disorder that typically causes hypertension, hypokalaemia, primary amenorrhoea, and the absence of secondary sex characteristics in 46, XX individuals. Partial 17-OHD is even rarer than complete 17-OHD and is prone to missed diagnosis due to its subtler symptoms. The aim of this study was to help early detection and diagnosis of partial 17-OHD. Methods: We present a case of a 41-year-old female (46, XX) patient with partial 17-OHD caused by a novel missense CYP17A1 mutation, c.391 A > C (p.T131P). This patient experienced hypertension, hypokalaemia and adrenal hyperplasia, but did not present with primary amenorrhoea or absence of secondary sex characteristics. Initially, she was misdiagnosed and underwent right and left adrenalectomy, but the procedures were ineffective. Afterward, she received a one-month treatment of 0.5 mg dexamethasone, which greatly relieved her symptoms. Additionally, we reviewed reports of thirteen other patients with partial 17-OHD in 46, XX individuals from the literature, totalling fourteen probands. Results: We found that primary amenorrhoea, hypertension, hypokalaemia, and ovarian cysts accounted for 15.4%, 42.9%, 38.5%, and 72.7% of these patients, respectively. In contrast, elevated serum progesterone was present in all patients. Conclusion: Based on our literature review, the absence of primary amenorrhoea, hypertension or hypokalaemia cannot rule out suspicion for 17-OHD in 46, XX individuals. However, an elevation in serum progesterone levels is a highly sensitive indicator for diagnosing 17-OHD. Plain language summary: What is the context?: 17-OHD is a rare cause of secondary hypertension, often with hypokalaemia, primary amenorrhoea and absence of secondary sex characteristics. Partial 17-OHD is an even rarer subtype of 17-OHD, with subtler symptoms. There are few reports concerning partial 17-OHD, especially in 46, XX patients. What is new?: We reported a case of a 46, XX patient with partial 17-OHD caused by a novel missense CYP17A1 mutation, c.391 A > C (p.T131P). We also conducted a literature review to summarise the clinical, hormonal and genetic characteristics of fourteen 46, XX probands with partial 17-OHD. From the literature review, we found that: Most 46, XX patients with partial 17-OHD presented with partial pubic hair, breast development, oligomenorrhea or secondary amenorrhoea, normotension, and/or normokalemia. All 46, XX patients with partial 17-OHD presented with elevated serum progesterone. However, the relationship between in vitro enzyme activities of the 17-hydroxylase and/or17, 20-lyase and clinical severity is still unclear. What is the impact?: The current study can help early detection and diagnosis of partial 17-OHD.